Diversity and preserved shell coloration patterns of Miocene Conidae (Neogastropoda) from an exposure of the Gatun Formation, Colón Province, Panama. (24th May 2018) - Hendricks, Jonathan R.
Abstract: Extant members of the neogastropod family Conidae (cone snails) are renowned for their often dazzling shell coloration patterns and venomous feeding habits. Many cone snail species have also been described from the fossil record, but to date have been little used to understand the evolutionary history of extant clades. The cone snail fauna of the Miocene Gatun Formation of Colón Province, Panama is especially important for understanding the temporal and biogeographic history of tropical American Conidae. Intensive, focused collecting from an exposure of the lower Gatun Formation (deposited ca. 11–10 Ma) resulted in the discovery of nearly 900 specimens of Conidae. Remarkably, many of these well-preserved specimens exhibit revealed coloration patterns when exposed to ultraviolet light. The fluorescing coloration patterns were used in conjunction with other features of shell morphology to differentiate species and, in most cases, evaluate their potential relationships to members of the extant tropical American fauna. Nine species are fully described from this locality, one of which is recognized as new: Conus ( Stephanoconus ) woodringi n. sp. At least one, and perhaps more, additional Conidae species are also present at the study locality. The diversity of this Conidae fauna is considered moderate relative to other recently analyzed tropical American fossil assemblages. The phylogenetic diversity of the assemblage, however, is noteworthy: six of the ten species can be confidently assigned to six different clades of extant Conidae, providing potentially useful calibration points for future phylogenetic studies. http://zoobank.org/8fe00c31-8f3f-4514-85af-29068e468cd3